Efeitos comportamentais e neuroquímicos do 1,8-cineol em modelos de ansiedade com camundongos - Oliveira, Milena Fontenele de (2024)
Anxiety disorders group a set of psychological disorders that are characterized by common signs and symptoms. In the emotional sphere, there is fear, anxiety and stress that are disproportionate to the context. The family, work and relationship spheres have been shown to be the main harms in an anxious situation, thus compromising the quality of life of patients. As for traditional psychotropic drugs, despite playing a unique role in controlling symptoms, they can generate adverse effects on patients, which reduce the chances of therapeutic adherence. Therefore, it is necessary to search for alternative substances that are effective in treating patients with anxiety disorders, whose side effects are less harmful. In the present study, we investigated the effects of 1,8-cineole (CIN) in predictive models of anxiety, such as the Elevated Plus Maze Test and the Light/Dark Box Test. For this, male Swiss mice were treated for 14 days with CIN at doses of 5, 10 and 25 mg/kg, Diazepam 1 mg/kg or saline. The behavioral evaluation showed that CIN at a dosage of 5 mg/kg had an anxiolytic-like effect in the Elevated Cross Maze and Light/Dark Box tests and improved the animals' exploratory capacity, evidenced by the Perforated Plate and Open Field tests. In neurochemical analysis, it reduced malondialdehyde levels and nitrite/nitrate levels, especially at a dosage of 5 mg/kg, showing antioxidant and modulating activity of the endogenous antioxidant system. Furthermore, it was shown that CIN acts via the GABAA receptor, data presented through the use of the drug flumazenil, an antagonist of this GABAergic receptor. It is concluded that the present work provided preclinical evidence of CIN as a new therapeutic approach to be used in the treatment of neuropsychiatric disorders such as anxiety disorders.